Abiotic factors determine the root system architecture – review and update - Ewa Młodzińska-Michta (Acta Societatis Botanicorum Poloniae, 2023)
Decades of root research have led to a deep understanding of the molecular and genetic mechanisms regulating root system architecture. This review provides past and present-day root research with a focus on abiotic factors, such as nutrient limitation, excess of nutrients, water, salinity, temperature, light, selected heavy metals, and hazardous contaminations which affected primary and lateral root growth. It also briefly summarized current knowledge about the molecular machinery involved in the modulation of RSA of the modern root system of dicot species, such as Arabidopsis thaliana .